«FOREIGN LANGUAGES IN THE FIELD OF PHYSICAL EDUCATION AND SPORTS INNOVATIVE METHODS IN LEARNING MULTIMEDIA AND INFORMATION TECHNOLOGY» - Mutalibova Madinabonu Baxtiyorjon qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article discusses innovative methods used in the study of foreign languages based on multimedia and computer information technology for students of the Uzbek State University of Physical Culture and Sports. It is also noted that the demand for the introduction of new methods is high, in contrast to the usual methods used in education. The relevance of the use of new innovative methods and the problems of their integration into the educational process were also discussed. The role of the teacher in the updated learning process with innovative methods is described.